2017
DOI: 10.1142/s012906571750023x
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Quiet Sleep Detection Approach in Preterm Infants as a Gateway to Assess Brain Maturation

Abstract: Sleep state development in preterm neonates can provide crucial information regarding functional brain maturation and give insight into neurological well being. However, visual labeling of sleep stages from EEG requires expertise and is very time consuming, prompting the need for an automated procedure. We present a robust method for automated detection of preterm sleep from EEG, over a wide postmenstrual age (PMA = gestational age + postnatal age) range, focusing first on Quiet Sleep (QS) as an initial marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 52 publications
2
66
0
Order By: Relevance
“…Stefanski et al [36] found an overall agreement of 87% for scoring EEG sleep patterns, whereas the agreement was 10% lower for coding behavioural patterns, and decreased with lower GA. In our own cohort of preterm infants (PMA 27–41 weeks), we found a Cohen's Kappa of 0.93 (95% CI: 0.90–0.95) for QS versus non-QS classified epochs, with the lowest Kappa value for 27–31 weeks PMA [37]. Nevertheless, scoring all different sleep states will be more challenging and induce higher disagreement when characterizing immature sleep patterns, since strict criteria for scoring sleep in preterm infants are lacking [38].…”
Section: Sleep Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Stefanski et al [36] found an overall agreement of 87% for scoring EEG sleep patterns, whereas the agreement was 10% lower for coding behavioural patterns, and decreased with lower GA. In our own cohort of preterm infants (PMA 27–41 weeks), we found a Cohen's Kappa of 0.93 (95% CI: 0.90–0.95) for QS versus non-QS classified epochs, with the lowest Kappa value for 27–31 weeks PMA [37]. Nevertheless, scoring all different sleep states will be more challenging and induce higher disagreement when characterizing immature sleep patterns, since strict criteria for scoring sleep in preterm infants are lacking [38].…”
Section: Sleep Monitoringmentioning
confidence: 99%
“…8). This leads to a globally more continuous EEG and the relative change in discontinuity between QS and non-QS states is only minor [37,47]. A regular respiratory rate and no REMs are the most consistent non-cerebral features associated with QS.…”
Section: Development Of Neonatal Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…After quantifying the multiscale entropy of each EEG channel, four features were extracted from the multiscale entropy curve: (1) the area under the multiscale curve (this will be referred to as the complexity index); (2) the average slope of the multiscale entropy curve in the small scales (scale 1-5); (3) the average slope of the curve in the large scales (scale [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; and (4) the maximum value of the multiscale entropy curve. Thus, in total, a set of 32 (8 channels × 4) features are extracted.…”
Section: Feature Extractionmentioning
confidence: 99%
“…The second dataset comprised 25 preterm infants, with gestational age (GA) ≤ 32 weeks, who were recruited for a larger EEG study to assess brain development and automatically detect quiet sleep epochs [20,21]. Each patient was enrolled with informed parental consent at the Neonatal Intensive Care Unit (NICU) of the University Hospital of Leuven, Belgium.…”
Section: Eeg Datamentioning
confidence: 99%